Cultural Guidelines for Commercial Production of Interiorscape Aglaonema - Jianjun Chen; Dennis B. McConnell; Richard J. Henny; Kelly C. Everitt (EDIS)
The intent of this article is to describe common Aglaonema species and cultivars in the foliage plant industry, provide guidelines on their culture and interior use, and list physiological problems encountered in both production and in the interiorscape. This document is ENH957, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 30, 2003.